Longitudinal Study on the Expectations of Cloud Computing Benefits and an Integrative Multilevel Model for Understanding Cloud Computing Performance ￼ - Tomi Dahlberg; Hannu Kivijärvi; Timo Saarinen (United States, 2022)
Cloud computing, a term introduced ten years ago, has proliferated rapidly both in developed and developing economies. Benefit expectations have impacted the rapid usage increase of this technology. We investigated with a five-year longitudinal survey changes in the expectations regarding cloud computing. We also crafted an integrated multilevel model to understand how cloud expectations and cloud readiness influence cloud computing deployment and performance combined with five IT business value (ITBV) factors. We tested empirically the crafted hypotheses and the research model using survey data collected from approximately 200+200 randomly selected business and IT executives in 2014 and 2015. Empirical results confirmed that our research model explained approximately one half of cloud computing performance for both years.
Hawaii International Conference on System Sciences 2017 (HICSS-50):